ENSURING SAFETY OF PARTICIPANTS IN CRIMINAL PROCESSES DURING COURT TRIAL - A.Umarkhanov (Scholar Express Journals, 2024)
This scientific article is aimed at explaining the scientific basis of ensuring the safety of the participants in the criminal proceedings during one of the important stages of the process. In this, the problems and achievements of ensuring the security of the participants participating in the trial were highlighted. In revealing the topic, the author's approaches to ensuring the safety of the participants were developed based on the analysis of existing researches, legal bases and practical materials. Also, in the era of today's advanced technologies, the issue of ensuring the safety of the participants of the process is not undermined by the principles of equality.
Keywords: court; criminal proceedings; discussion